If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3x + 6 = 4x + 1 Reorder the terms: 9 + 6 + -3x = 4x + 1 Combine like terms: 9 + 6 = 15 15 + -3x = 4x + 1 Reorder the terms: 15 + -3x = 1 + 4x Solving 15 + -3x = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + -3x + -4x = 1 + 4x + -4x Combine like terms: -3x + -4x = -7x 15 + -7x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -7x = 1 + 0 15 + -7x = 1 Add '-15' to each side of the equation. 15 + -15 + -7x = 1 + -15 Combine like terms: 15 + -15 = 0 0 + -7x = 1 + -15 -7x = 1 + -15 Combine like terms: 1 + -15 = -14 -7x = -14 Divide each side by '-7'. x = 2 Simplifying x = 2
| 4x-(2x-5x)+100=800 | | 24s-18= | | 3x-188=11x+122 | | -16k^6-20k^5=0 | | (x-5-7i)(x-5+7i)= | | -7-17=-13y-11 | | 9y=6+4X | | 1048.8=23*x | | 3x^3+30=0 | | Y=(x-5)(x-5)+3 | | x+2-2=5 | | X^3+3x^2=24x+72 | | -x-3=-3x+3 | | 5y^2+4-12=0 | | 5.2=4x-1.2 | | (x-5-7i)(x-5+7i)=0 | | 2x-3+12x=15+7x-4 | | y=2x+55 | | 12+2x=-18 | | 108=12(X+3) | | y/5-3.4=-15.9 | | 2x^3-5x^2+40x-100=0 | | 2x+5.5y=17 | | -6+x=6-3x | | 12a-14=8 | | (2y-6)+y=180 | | 81x^4=3x | | -7-z=12-z | | a=1+8*2+(8-4)*7 | | 4x(3x)+5-7=56 | | -3x+7=5-4x | | -6x-13=-61 |